PENERAPAN INDIKATOR NASIONAL MUTU RUMAH SAKIT DIHUBUNGKAN DENGAN DIMENSI MUTU PELAYANAN DI RUMAH SAKIT UMUM SEMBIRING TAHUN 2023 - Hardianti, Ema; Kasim, Felix; Ariani, Peny (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
The development of the current era makes people become more active in seeking information about health. Hospital service quality has two components, namely compliance with predetermined quality standards and fulfillment of customer satisfaction. The purpose of this study was to determine the application of national indicators of Hospital Quality in relation to the service quality dimensions of Sembiring Deli Tua General Hospital. The type of research used in this study was quantitative analytic in nature with a Cross Sectional design with a total sample of 72 people. Data collection using a questionnaire. Data analysis used univariate analysis and bivariate analysis using Chi-Square test at 95% confidence level, α=5%. The results of the study showed that the implementation of national indicators of hospital quality based on good effectiveness was 51.4%, based on good category safety was 55.6%, based on good category orientation was 58.3%, based on timely category was not good at 58.3% , based on good category efficiency of 54.2%, based on good integrated category of 56.9%, good category hospital quality of 47.2%. This study shows that there is a relationship between the implementation of national hospital quality indicators and the dimensions of hospital service quality based on effectiveness (p=0.010), based on safety (p=0.023), based on patient orientation (p=0.039), based on timeliness (p= 0.046), based on fairness (p=0.020). The results of the study suggest that hospital management creates a climate of healthy competition, by giving awards in the form of salary bonuses every 6 months or empowering nurses who have worked as trainers/instructors for a long time or with good performance in the form of promotions, incentives, and others. .